ANALYSIS OF OCCUPATIONAL HEALTH AND SAFETY RISK IN THE 76MM SHOOTING PROCESS USING HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL (HIRARC) METHODS - Dwi Prasetyo (Journal of Industrial Engineering & Management Research, 2023)
The Meriam Otomelara 76 mm is a strategic weapon of the KRI which functions as an anti-surface and anti-aircraft weapon owned by the Ahmad Yani or Van Speijk class of KRI. The high usage of the 76mm gun during exercises, as well as the age of the KRI and its weapon system, can affect the success of training tasks and create the risk of work accidents that can harm personnel and material. To anticipate work accidents in the KRI and base environment, the Indonesian Navy has launched the "Zero Accident" program. This program contains preventive attitudes and actions, as well as anticipation of events or accidents that could cause losses to personnel and material. The program is also expected to prevent risks or dangers to the safety and health of all Indonesian Navy personnel. To reduce or prevent the risk of work accidents during the 76mm gun firing process, identification and risk assessment of hazards that arise are carried out, followed by control measures. The method used in this research is the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. From the results of calculations and analysis using the HIRARC method, there are three hazards that have a high risk level and require control measures before work is carried out. These hazards are slippery hands, which cause ammunition to fall and hit crew members, slippery stairs, which cause personnel to slip and injure themselves while lifting ammunition from the warehouse, and the hazard of incorrect procedures in handling jammed ammunition, which can cause ammunition to explode and cause burns to gun crew members.